2020
DOI: 10.1155/2020/7316257
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella catarrhalis: A Cause of Concern with Emerging Resistance and Presence of BRO Beta-Lactamase Gene—Report from a Tertiary Care Hospital in South India

Abstract: Background. Found as a commensal in the upper respiratory tract, Gram-negative diplococcus Moraxella catarrhalis did not hold much importance as an infectious agent for long. The emergence of the first antibiotic-resistant strain of M. catarrhalis was noted in 1977 in Sweden. This has gradually spread worldwide over the years to more than 95% of the strains showing resistance to penicillin now. Penicillin resistance is mediated by the production of beta-lactamases encoded by bro-1 and bro-2 genes that code for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…22 In this study, amoxicillin/ clavulanate resistance was low, and this was in tandem with finding in India. 32 This study also showed low resistance to cefuroxime, an observation that was also made in a study conducted in Columbia. 33 This finding suggests that this antibiotic may be useful for the treatment of pneumonia in children in the study setting.…”
Section: Discussionsupporting
confidence: 79%
“…22 In this study, amoxicillin/ clavulanate resistance was low, and this was in tandem with finding in India. 32 This study also showed low resistance to cefuroxime, an observation that was also made in a study conducted in Columbia. 33 This finding suggests that this antibiotic may be useful for the treatment of pneumonia in children in the study setting.…”
Section: Discussionsupporting
confidence: 79%
“…Moraxella is a pathogen that is susceptible to most beta-lactamase stable antibiotics and fluoroquinolones [8][9][10][11]. The choice of antimicrobial agents depends on the age of the patient, comorbid conditions, and desired antimicrobial coverage [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moraxella catarrhalis is a pathogenic gram-negative bacterium coccus of the Neisseriae family usually colonises the upper respiratory tract and thereby causing infection ranging from otitis media in children and downstream respiratory infection in adult. This bacterium has become greatly resistant to penicillin antibiotic (Savitha et al, 2020). Salmonella typhi is a Gram-negative, aerobic, rod-shaped bacterium known to be involved in salmonellosis and the disease is usually contracted in contaminated food stuffs (especially in meat) by this organism (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%